Galectins and Their Ligand Glycoconjugates in the Central Nervous System Under Physiological and Pathological Conditions - Nio-Kobayashi, Junko; Itabashi, Tetsuya (Frontiers in Neuroanatomy, 2021)
Galectins are beta-galactoside-binding lectins consisting of 15 members in mammals. Galectin-1, -3, -4, -8, and -9 are predominantly expressed in the central nervous system (CNS) and regulate various physiological and pathological events. This review summarizes the current knowledge of the cellular expression and role of galectins in the CNS, and discusses their functions in neurite outgrowth, myelination, and neural stem/progenitor cell niches, as well as in ischemic/hypoxic/traumatic injuries and neurodegenerative diseases such as multiple sclerosis. Galectins are expressed in both neurons and glial cells. Galectin-1 is mainly expressed in motoneurons, whereas galectin-3-positive neurons are broadly distributed throughout the brain, especially in the hypothalamus, indicating its function in the regulation of homeostasis, stress response, and the endocrine/autonomic system. Astrocytes predominantly contain galectin-1, and galectin-3 and -9 are upregulated along with its activation. Activated, but not resting, microglia contain galectin-3, supporting its phagocytic activity. Galectin-1, -3, and -4 are characteristically expressed during oligodendrocyte differentiation. Galectin-3 from microglia promotes oligodendrocyte differentiation and myelination, while galectin-1 and axonal galectin-4 suppress its differentiation and myelination. Galectin-1- and -3-positive cells are involved in neural stem cell niche formation in the subventricular zone and hippocampal dentate gyrus, and the migration of newly generated neurons and glial cells to the olfactory bulb or damaged lesions. In neurodegenerative diseases, galectin-1, -8, and -9 have neuroprotective and anti-inflammatory activities. Galectin-3 facilitates pro-inflammatory action; however, it also plays an important role during the recovery period. Several ligand glycoconjugates have been identified so far such as laminin, integrins, neural cell adhesion molecule L1, sulfatide, neuropilin-1/plexinA4 receptor complex, triggering receptor on myeloid cells 2, and T cell immunoglobulin and mucin domain. N-glycan branching on lymphocytes and oligodendroglial progenitors mediated by beta1,6-N-acetylglucosaminyltransferase V (Mgat5/GnTV) influences galectin-binding, modulating inflammatory responses and remyelination in neurodegenerative diseases. De-sulfated galactosaminoglycans such as keratan sulfate are potential ligands for galectins, especially galectin-3, regulating neural regeneration. Galectins have multitudinous functions depending on cell type and context as well as post-translational modifications, including oxidization, phosphorylation, S-nitrosylation, and cleavage, but there should be certain rules in the expression patterns of galectins and their ligand glycoconjugates, possibly related to glucose metabolism in cells.